Investigation of flowering phenology, pollinator and invertebrate biodiversity value on urban green roofs and an evaluation of ornamental horticulture crops for pollinator value - Guidi, Michael A., author; Bousselot, Jennifer, advisor; Hufbauer, Ruth, committee member; Krishnan, Sarada, committee member (Colorado State University. Libraries, 2024)
Urban green space, green infrastructure, and horticultural installations are gaining recognition for their potential to foster biodiversity. Green roofs are challenging growing environments for plants, characterized by extreme substrate temperatures, high light intensity, limited moisture availability, and limited substrate depth. Plants have a variety of physiological responses to these unique conditions, but little is known about how green roof growing conditions affect ecological characteristics like plant flowering phenology. Similarly, studies are only just beginning to uncover the degree to which green roofs can provision habitat and support urban biodiversity. We evaluated the flowering phenology and made in-situ pollinator observations of 15 plant taxa growing both on green roof systems and at ground level at the Denver Botanic Gardens over two growing seasons. Using the same study sites, we sampled invertebrate diversity on green roof sites and ground level using pitfall traps. Finally, using a large citizen-science dataset, we evaluated differences in pollinator visitation with a specific focus on plant nativity, cultivated origin, growth form. We found that flowering phenology is substantially earlier on green roofs compared to ground level. We also observed a greater number of pollinators on green roofs early in the season, compared to ground level, presumably due to the availability of flora resources among the observed plant taxa. We observed significantly higher substrate temperatures along with wider diurnal temperature amplitude during the growing season that may contribute to this pattern. Invertebrate abundance was substantially higher at ground-level, species richness was similar between the intensive green roof and ground-level, and we observed substantially lower abundance and richness on the extensive green roof. Divergence in flowering phenology between individual plants of the same species on green roofs and plants at ground-level may have implications for organisms that rely on floral resources in urban environments. Earlier flower initiation on green roofs may provide pollinators with unique foraging opportunities and aid targeted conservation where early-season floral resources are limited. Similarly, results from invertebrate sampling suggest that green roofs, especially intensive roofs with high vegetation coverage, species richness, and habitat heterogeneity may offer invertebrate habitat on par with ground-level urban gardens and may even support unique groups of invertebrate taxa. Our results from our citizen science pollinator observations demonstrate that non-native plants showed similar visitation compared to native plants, but origin was important with selections and species having significantly higher pollinator visitation compared to hybrid plants. Shrubs and herbaceous perennials demonstrated high pollinator visitation compared to other plant growth forms.